Incidental abdominal lymph node metastases from a known breast cancer in resected specimen of invasive pancreatic ductal adenocarcinoma: report of a case - Taniai, Tomohiko (Int Cancer Conf J, 2019)
Breast cancer is known to metastasize to all organs of the body. However, abdominal lymph node metastases from breast cancer are extremely rare. We herein report a resected case of an invasive pancreatic ductal adenocarcinoma (PDAC) in which abdominal lymph node metastases from breast cancer were diagnosed. A 54-year-old woman was pointed out to have a tumor in the pancreatic tail with dilatation of the distal pancreatic duct. She had undergone partial mastectomy for left breast cancer at the age of 51 years and had undergone partial liver resection for liver metastasis in the segment 3/4 6 months earlier. Computed tomography revealed a low-density tumor in the pancreatic tail with dilated distal main pancreatic duct. Magnetic resonance imaging (MRI) exhibited a high-intensity tumor in the pancreatic tail in diffusion-weighted images. With a diagnosis of pancreatic cancer, distal pancreatectomy and splenectomy with lymph nodes dissection was performed. Lymph node metastases along the splenic artery were pathologically similar to PDAC. However, lymph node metastases along the left gastric artery, common hepatic artery, celiac axis, and superior mesenteric artery were pathologically similar to breast cancer. Immunohistochemistry staining of abdominal lymph nodes with GATA-3 was positive, which strongly suggested metastatic breast cancer. Although she received chemotherapy with S-1 for breast cancer and PDAC for 4 months, MRI showed multiple liver metastases derived from breast cancer. Finally, she died 12 months after operation.